O Direito Comercial Reconstruído:interpretação e aplicação pelos princípios e sua efetividade com o processo empresarial - Furtado, João Rafael de Farias (2016)
This thesis aims to demonstrate the need for reconstruction the Commercial Law, as it proposes its interpretation/application by the principles, developing its own procedural tool that comes from an autonomous process of law, which is called commercial process. Thus, this thesis studies the history of Commercial Law, in what is called the Old and New Commercial Law, defending their autonomy and discoursing on how to organize their legal rules and principles. It was also discussed about the legal uncertainty that faces entrepreneurs in their judicial disputes, which leads to no incentive or interest to the private investment, especially when it is observed that the operators of the Commercial Law have not followed the principles paradigm held by the Federal Constitution of 1988, where the principles were placed in the center of the legal system. This fact led to interpretation/misapplication of the rules of the Commercial Law, causing an unpredictable environment in judicial decisions, which increases the cost of goods and services in Brazil. It is in this context that aims to rebuild the Commercial Law, stating and describing its principles, but without forgetting about their legal rules. However, in order to give effectiveness to the Commercial Law Reconstructed, is not enough the enunciation of its principles, but is also required regulate the Commercial Law Procedure, which through its own process, given the its peculiarities, can guarantee effectiveness in the Commercial Law